Proposal of a scheme for the production, maintenance and utilization of citrus certified propagative material in the Mediterranean - D'Onghia A.M.; Savino V.; Kyriakou A.P. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
A draft of a possible common Mediterranean certification scheme of citrus propagating material is given as the final product of three years of networking activity. The basic of the protocol, taking into account the requirements characterizing other European certification schemes and the actual problems of citrus occurring in the Mediterranean, is described in all phases concerning the production and the utilization of healthy propagative materials. Emphasis is given to the sanitary requirements and controls to be included in the protocol.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)